2021
DOI: 10.1111/bioe.12891
|View full text |Cite
|
Sign up to set email alerts
|

Intentional machines: A defence of trust in medical artificial intelligence

Abstract: Trust constitutes a fundamental strategy to deal with risks and uncertainty in complex societies. In line with the vast literature stressing the importance of trust in doctor–patient relationships, trust is therefore regularly suggested as a way of dealing with the risks of medical artificial intelligence (AI). Yet, this approach has come under charge from different angles. At least two lines of thought can be distinguished: (1) that trusting AI is conceptually confused, that is, that we cannot trust AI; and (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 0 publications
0
37
0
Order By: Relevance
“…The principles of the EU guidelines for trustworthy AI or the proposed criteria of computational reliabilism by Durán and Formanek can be seen as attempts to grasp trustworthiness. 36 Similarly, drawing on the Daniel Dennett's model of three stances, Starke et al 37 have recently suggested a dimensional model that can help disentangle different aspects of trustworthiness with view to reliability, competence, and intentions. In the context of medical AI, these aspects help scrutinize a system asking whether it works under the specified conditions, how well it performs in a particular task, and whether the "intentions" of the system, as imbued in it by the developers, are compatible with the intentions of the AI user.…”
Section: Trust and Trustworthinessmentioning
confidence: 99%
“…The principles of the EU guidelines for trustworthy AI or the proposed criteria of computational reliabilism by Durán and Formanek can be seen as attempts to grasp trustworthiness. 36 Similarly, drawing on the Daniel Dennett's model of three stances, Starke et al 37 have recently suggested a dimensional model that can help disentangle different aspects of trustworthiness with view to reliability, competence, and intentions. In the context of medical AI, these aspects help scrutinize a system asking whether it works under the specified conditions, how well it performs in a particular task, and whether the "intentions" of the system, as imbued in it by the developers, are compatible with the intentions of the AI user.…”
Section: Trust and Trustworthinessmentioning
confidence: 99%
“…Trust is a relational concept—a disposition or intentional attitude—which is associated with situations of uncertainty, relations of dependency and expectations about future behaviour/intentions [ 1 ]. If trust is regarded as a feature of relationships, such that A (truster) trusts B (trusted) to X [ 2 , 3 ], then trust is A’s attitude regarding B and trustworthiness is an aspect of B namely, “…the commitments, virtues, traits or features [of B] that ground justified or well-placed trust” [ 4 : 24]. Consequently, if B is perceived as, for example: dishonest, incapable of keeping a confidence and performing inconsistently and incompetently, then they will be deemed untrustworthy, as someone that one would not enter into a trust relationship with.…”
Section: Introductionmentioning
confidence: 99%
“…According to Bauer [ 5 ], trust is “..a belief formed as a result of probabilistic reasoning…a probability that quantifies a belief that the trusted person will in fact do what one is expecting her to do.” [p4], namely, A trusts B because she believes (there is a high probability) that B will X. Likewise, Starke et al [ 3 ] observe that trust is necessary to deal with uncertainty. They point out that in addition to the uncertainty about whether B will X or not X, trust comes into play when A occupies an uncertain or vulnerable relationship with B; A is dependent upon B’s good will to X [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations